2003
DOI: 10.1128/mcb.23.24.9032-9045.2003
|View full text |Cite
|
Sign up to set email alerts
|

Anoxic Fibroblasts Activate a Replication Checkpoint That Is Bypassed By E1a

Abstract: Little is known about cell cycle regulation in hypoxic cells, despite its significance. We utilized an experimentally tractable model to study the proliferative responses of rat fibroblasts when rendered hypoxic (0.5% oxygen) or anoxic (<0.01% oxygen). Hypoxic cells underwent G 1 arrest, whereas anoxic cells also demonstrated S-phase arrest due to suppression of DNA initiation. Upon reoxygenation, only those cells arrested in G 1 were able to resume proliferation. The oncoprotein E1a induced p53-independent ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 58 publications
(86 reference statements)
2
20
1
Order By: Relevance
“…5,26 Further, it has been previously demonstrated that hypoxia causes cell cycle growth arrest in G1 in nontransformed cells. [16][17][18] Our data, however, show that the reduced viral yield under hypoxic conditions was not due to cell cycle arrest of tumor cells. Although as anticipated, hypoxia was able to growth arrest normal HUVEC, hypoxia did not growth arrest the cancer cells.…”
Section: Hypoxia Reduces Adenoviral Replicationcontrasting
confidence: 48%
See 1 more Smart Citation
“…5,26 Further, it has been previously demonstrated that hypoxia causes cell cycle growth arrest in G1 in nontransformed cells. [16][17][18] Our data, however, show that the reduced viral yield under hypoxic conditions was not due to cell cycle arrest of tumor cells. Although as anticipated, hypoxia was able to growth arrest normal HUVEC, hypoxia did not growth arrest the cancer cells.…”
Section: Hypoxia Reduces Adenoviral Replicationcontrasting
confidence: 48%
“…[16][17][18] Although the exact mechanism is still debated, hypoxia generally reduces the activity of cyclin-dependent kinases, which leads to hypophosphorylation of the Rb protein and growth arrest in G1. [16][17][18] Moreover, the presence of cells in S-phase may be important to enable adenoviral replication. 19,20 To Figure 1 HIF-1a is expressed under hypoxic conditions.…”
Section: Hypoxia Does Not Reduce the Proportion Of Cells In S-phasementioning
confidence: 99%
“…For example, most normal cells and many neoplastic cells undergo a growth arrest when hypoxic, whereas some stem cells and neoplastic cells continue to proliferate under hypoxic conditions (7,8). Studies have also suggested that hemangioblasts, renal tubular cells, and embryonic stem cells all differentiate when hypoxic, while hypoxic adipocytes and hematopoietic stem cells are resistant to differentiation (9 -12).…”
mentioning
confidence: 99%
“…For example, fibroblasts can replicate at oxygen levels below 25 mm Hg (ϳ1.13 mg/liter), but their capacity for hydroxylation of proline and lysine, which is required for collagen synthesis, is impaired. Cell replication is arrested at oxygen levels below 0.5% (approximately 0.16 mg/liter) (17). Furthermore, angiogenesis in chronic wounds also requires oxygen.…”
mentioning
confidence: 99%